Constraints in Availing the Livestock Extension Services under state Department of Animal Husbandry as perceived by women Livestock Farmers - Yadav , Jyoti; Tripathi , Hema; Balaraju , B. L.; Yadav, Rekha (Indian Journal of Extension Education, 2017)
Livestock sector is one of the most important sources of livelihood in rural domain and livestock farming is mainly under  the control of rural women at household level. But unfortunately, they have least access to livestock extension services.  There are many constraints which are being faced by women livestock farmers in availing the livestock extension  services. To explore these constraints, the current research was done in four districts of central plain zone of Uttar Pradesh.  A multi-stage random sampling technique was employed for the selection of women livestock farmers. Data were  collected from randomly selected 200 women livestock farmers from 8 villages. Lack of training related to scientific  livestock rearing was ranked first in the constraints perceived by women livestock farmers in availing the livestock  extension services followed by lack of awareness on government livestock extension programmes/schemes (rank II) and  lack of time to attend livestock extension meeting, goshties, camp etc. (rank III).
Keywords: Livestock extension services; constraints and women livestock farmers